Spatial sampling strategies for mapping a volcanic ground water plume in Sierra Valley, California. - Luzzadder-Beach, Sheryl (Professional Geographer, 1997)
A study was conducted to compare the relative values of three field sampling strategies for mapping a known migrating plume of volcanic ground water in Sierra Valley, California. Computer mapping and GIS software were used to generate kriged grid files and digital contour maps displaying the concentration of electrical conductivity in the basin for different years. Findings revealed that the first strategy, which sampled wells once each year during 1957, 1972, and 1980, indicated spatial-temporal changes in ground water quality more clearly on maps than did the two alternative sampling strategies. The second strategy sampled one well per township per year during 1957, 1972, and 1980 and failed to identify the migrating plume, despite being a recommended strategy. The third strategy, which frequently sampled in time a small, fixed group of indicator wells every four years for the same period, again created maps bearing little resemblance to the original pattern revealed by the first strategy.